Saturation effect on the distribution of rill detachment rate. (10th March 2021) - Huang, Yuhan; Wang, Wei; Lei, Tingwu; Li, Fahu; Li, Juan
Abstract: Detachment rate in rill erosion is an important indicator of soil erosion speed and serves as the basis for estimation of soil erosion using the process‐oriented model. Rill detachment rates on saturated soil slopes were numerically calculated from the dataset of the rill erosion process. The datasets of sediment concentrations were obtained from laboratory experiments, along saturated soil rills 1, 2, 4 and 8 m under slope gradients of 5°, 10°, 15° and 20° and flow rates of 2, 4 and 8 L min −1, and were used to compute rill detachment rates through a numerical algorithm. The resulting rill detachment rates on saturated soil slopes ranged from 0.006 to 0.994 kg m −2  s −1 . Exponential functions fitted well the rill detachment rates with rill lengths, whereas linear functions fitted well those with sediment concentrations. The rill detachment rate patterns of saturated soil slopes exhibited similar rill erosion–sediment concepts to those of non‐saturated soil slopes. However, saturated soil slopes were detached considerably faster than the non‐saturated soil slopes. Detachment rates of saturated soil rills were initially and considerably more rapid and decreased faster with rill length than those of non‐saturated soil rills. The saturated soil rills detached 1.627 to 2.246 times the sediments of the non‐saturated soil rills. This phenomenon indicates that faster rill detachments in saturated soil rills make sediment loads in water approach the sediment transport capacities faster than those in non‐saturated soil rills. The computed detachment rates and the functional relationships in this work can provide a basis for determining rill erosion model parameters on saturated soil slopes. Highlights: Detachment rate of saturated rill can be computed similarly to non‐saturated rill. Rill detachment rate is well correlated to sediment concentration and rill length. Soil particles in saturated rill are detached considerably faster than non‐saturated rill.